Price discovery of climate risk and green bonds: A dynamic information leadership share approach - Hou, Y.; Xu, D.; Oxley, Leslie; Goodell, J.W. (2024)
This study investigates the price discovery of a novel stock market climate risk indicator, measured by the Morgan Stanley Capital International Climate Change Index (MSCI CCI) and global green bond indices. A time-varying information leadership share (ILS) measure assesses dynamic price discovery performance of the MSCI CCI and green bonds. We find that the MSCI CCI index dominates in the price discovery process in terms of time-varying ILS, despite the static result indicating the opposite. Further, the outbreak of the COVID-19 pandemic had restrictively positive effects on price discovery as the crisis progressed.